'More extraordinary than mundane … ' A phenomenological analysis of the experiences of individuals living with CLE and their taking care in the sun. (November 2020) - McGarry, Bláithín; O'Kane, Donal; McCourt, Collette; Gormley, Gerard J
Introduction: CLE is a chronic inflammatory autoimmune condition of which photosensitivity is a major symptom. Individuals living with CLE are advised to practice photoprotection. Despite the benefits for disease control, many individuals living with CLE do not practice optimal photoprotection. The aim of this study was to gain a deep insight into the lived experiences of individuals with CLE and their photoprotective practices. Methods: A qualitative study approach was conducted, using Hermeneutic phenomenology. Individuals living with CLE were recruited and interviewed. Rich pictures were used to enrich the interviews. Interviews were transcribed and analysed using Template Analysis. Results: Analysis revealed four themes: 'Much more than just a photosensitive skin condition', 'The impact of sun on CLE and social dynamics', 'Drifting to the sun: personal transitions and social norms' and 'Taking care in the sun: easier said than done'. Discussion and conclusion: This study provides a nuanced insight into the lived experiences of individuals with CLE and their photoprotective practices. Taking care in the sun is not a simplistic process. Beyond the biomedical model of illness, the social impact that CLE has on individuals has a dominant influence on their photoprotective behaviours. Such insights could help healthcare professionals tailor photoprotective advice.